2008
DOI: 10.1007/s11120-008-9347-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of the processes of molecular oxygen synthesis and electron transport in Ca2+-depleted PSII membranes

Abstract: Extraction of Ca(2+) from the O(2)-evolving complex (OEC) of photosystem II (PSII) membranes with 2 M NaCl in the light (PSII(-Ca/NaCl)) results in 90% inhibition of the O(2)-evolution reaction. However, electron transfer from the donor to acceptor side of PSII, measured as the reduction of the exogenous acceptor 2,6-dichlorophenolindophenol (DCIP) under continuous light, is inhibited by only 30%. Thus, calcium extraction from the OEC inhibits the synthesis of molecular O(2) but not the oxidation of a substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…Subsequent charge recombination in the dark reoxidizes Q A – (Figure d), and decreases the fluorescence yield to the low F 0 level again . It has been reported that the quantum yield of charge separation was decreased, and the kinetics of Q A – reoxidation were slowed by denaturing the oxygen-evolving complex of PSII . The yield of charge-separation of PSII for PSII/PGP20 was calculated as 0.89 ± 0.04, which is comparable to that for PSII in the solution system (0.91 ± 0.03).…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Subsequent charge recombination in the dark reoxidizes Q A – (Figure d), and decreases the fluorescence yield to the low F 0 level again . It has been reported that the quantum yield of charge separation was decreased, and the kinetics of Q A – reoxidation were slowed by denaturing the oxygen-evolving complex of PSII . The yield of charge-separation of PSII for PSII/PGP20 was calculated as 0.89 ± 0.04, which is comparable to that for PSII in the solution system (0.91 ± 0.03).…”
Section: Resultsmentioning
confidence: 50%
“…22 It has been reported that the quantum yield of charge separation was decreased, and the kinetics of Q A − reoxidation were slowed by denaturing the oxygenevolving complex of PSII. 25 The yield of charge-separation of PSII for PSII/PGP20 was calculated as 0.89 ± 0.04, which is comparable to that for PSII in the solution system (0.91 ± 0.03). The kinetics of Q A − reoxidation in PSII/PGP20 were similar to those of PSII in solution.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…It should be noted that in this work we used PSII particles without calcium, in which manganese catalytic center cannot oxidize water molecules to molecular oxygen. However, Ca-depleted PSII particles have a high electron transport speed (about 70% of the control (Semin et al 2008)). The reduction of the DCPIP arti cial acceptor is determined by electrons formed as a result of incomplete oxidation of water to hydrogen peroxide (Semin et al 2013).…”
Section: Resultsmentioning
confidence: 97%
“…В других случаях наблюдается «антиизоморфизм», при котором ион РЗЭ блокирует функцию Ca 2+ [Золин, Коренева, 1980]. Известно, что водоокисляющий комплекс ФС2 содержит ион Ca 2+ , удаление которого приводит к ингибированию кислород-выделяющей функции [Ghanotakis et al, 1984b;Semin et al, 2008]. Можно предположить, что ингибирование активности ФС2 ионами Tb 3+ связано с нефункциональным замещением иона Ca 2+ в водоокисляющем комплексе.…”
unclassified